Flood Risk Modeling in Buru Island, Maluku Province, Indonesia using Google Earth Engine: Pemodelan Risiko Banjir di Pulau Buru, Provinsi Maluku, Indonesia dengan menggunakan Mesin Google Earth - Susan E Manakane; Philia Christi Latue; Glendy Somae; Heinrich Rakuasa (MULTIPLE: Journal of Global and Multidisciplinary, 2023)
Flood Risk Modeling in Buru Island, Maluku Province, Indonesia using Google Earth Engine has made a significant contribution to addressing flood threats in the region. Through the integration of satellite imagery, topographic, and hydrological data, this analysis maps flood-prone areas and models their potential impacts. Data processing and analysis were conducted in Google Earth Engine. The results show that the area prone to flooding in the low class is 195,501.88 ha or 23.18%, the area in the medium risk class is 496,182.06 ha or 58.84% and the area at high risk of flooding is 151,599.17 ha or 17.98%. The modeling results provide insights into flood patterns and intensity, enabling the development of more effective mitigation strategies. The use of Google Earth Engine also enables the development of data-driven solutions to increase public awareness and contribute to holistic disaster management. This research not only impacts Buru Island, but also provides valuable guidance for flood risk mitigation efforts in similar areas